Ibn al-Haitham dan Perkembangan Instrumen Optik: Landasan Ilmu Falak Modern - Jannah, Elly Uzlifatul (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2024)
Ibn al-Haitham, a Muslim scientist from the 10th to 11th century CE, is known as a pioneer in the fields of optics and astronomy. His contributions to the development of modern science often receive insufficient attention, despite their significant impact. This study aims to explore the extent to which Ibn al-Haitham's thoughts influenced the development of Islamic astronomy, particularly in the context of optical instruments, using a literature review method. The results of the research show that Ibn al-Haitham adopted an experimental and mathematical approach to astronomy, which differed from the traditional views of his time. He critiqued Ptolemy's theory and made significant contributions to understanding astronomical phenomena such as eclipses and starlight. One of his significant achievements was the development of a method for determining the direction of the qibla using trigonometry, as well as the combination of empirical observation with mathematical analysis, which became the basis for the modern scientific method in astronomy. Ibn al-Haitham's influence on the development of Islamic astronomy is particularly evident in the evolution of optical instruments. His concept of the camera obscura became the foundation for the evolution of telescopes, theodolites, and instruments for observing the new moon. The optical principles he discovered played a major role in improving the accuracy of astronomical measurements and the development of more advanced observational technologies. His understanding of the behavior of light and image formation became the basis for the development of modern astronomical instruments. Although his thinking had some limitations, such as dependence on Aristotelian cosmological concepts, Ibn al-Haitham's contributions remain a critical foundation for the advancement of Islamic astronomy and astronomy as a whole. His progressive thinking and systematic scientific approach have had a long-lasting influence on the development of science. His intellectual legacy not only demonstrates his individual genius but also affirms the important role of Muslim scientists in advancing global scientific knowledge.